Coupled magnetic and ferroelectric domains in multiferroic Ni3V2O8. - Cabrera, I; Kenzelmann, M; Lawes, G; Chen, Y; Chen, W; Erwin, R; Gentile, T; Leão, J; Lynn, J; Rogado, N; Cava, R; Broholm, C (2009)
Electric control of multiferroic domains is demonstrated through polarized magnetic neutron diffraction. Cooling to the cycloidal multiferroic phase of Ni3V2O8 in an electric field E causes the incommensurate Bragg reflections to become neutron spin polarizing, the sense of neutron polarization reversing with E. Quantitative analysis indicates the E-treated sample has a handedness that can be reversed by E. We further show a close association between cycloidal and ferroelectric domains through E-driven spin and electric polarization hysteresis. We suggest that a definite cycloidal handedness is achieved through magnetoelastically induced Dzyaloshinskii-Moriya interactions.